MILK PRODUCTION AND BODY WEIGHT AT WEANING AND THEIR RELATIONSHIPS WITH BODY AND UDDER MEASUREMENTS IN MERIZ GOATS - . Y. Merkhan, K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
To investigate the correlation coefficients among the anatomical body structure and udder characteristics with each of body weight and milk production, 54 lactating Meriz does were randomly selected, kidded within 2 weeks in March, 2018. At weaning body weight as well as 6 body measurements and 8 udder and teat measurements were recorded. Also, Milk yield was recorded at weekly intervals till the does are dried-off. Results revealed moderate positive correlations between body measurements and milk production, while highest correlations were observed between udder measurements and milk production. Also, there was a strong positive correlation between body weight and body measurements. Four components were found meaningful; the first component was labeled as the ‘teat dimensions’ factor, ‘udder dimensions’ factor is a second component and the combination of the third and fourth component was interpreted as the ‘body dimensions’ factor. Therefore, the best predictors for body weight was rump height, heart girth and body length. Also, udder length, udder width, distance between teats and teat dimension were best predictors for milk production.